Reduction of cycles of bendamustine plus rituximab therapy in the cases with good response for indolent B‐cell lymphomas. Issue 4 (2nd May 2021) - Takezaki, Toshiaki; Nakazaki, Kumi; Toyama, Kazuhiro; Matsuda, Kensuke; Kogure, Yasunori; Chiba, Akira; Nakamura, Fumihiko; Honda, Akira; Kurokawa, Mineo
Abstract: Bendamusutine plus rituximab (BR) regimen is one of the standard regimens for indolent B‐cell lymphomas, yet the possibility of reduction of cycles of BR therapy without compromising therapeutic effects is not still uncovered. We retrospectively surveyed 57 cases including 40 follicular lymphoma cases who underwent BR regimen in our institute. The overall response (OR) rate and complete response (CR) rate were 86.0% (95% confidential interval (CI), 74.2–93.7) and 54.4% (40.7–67.6), respectively. Five‐year overall survival (OS) and 5‐years progression‐free survival (PFS) were 76.8% and 45.7%, respectively. We then grouped the patients by the number of administered cycles of BR regimen. PFS was significantly longer in 41 cases of the later cessation group (cycle 4–6) than in 16 cases of the earlier cessation group (cycle 1–3) ( p  = 0.012, 5‐years PFS; 46.8% vs. 35.2%, respectively), and both of OR and CR rate of the former was better than the latter (OR rate; 95.1% vs. 62.5%, p  < 0.01, CR rate; 61.4% vs. 31.3%, p  = 0.04). Interestingly PFS of twenty‐one (36.8%) cases receiving just 4 cycles was longer than that of 20 cases who received five or 6 cycles ( p  < 0.01, 5‐years PFS; 71.8% vs. 23.2%, respectively). Focusing on the group of four cycles, the 12 case with CR revealed longer PFS than seven cases with partial response (PR), and median PFS was not reached in CR cases and 16.9 months in the PR cases ( p  < 0.01). These results suggest that four cycles at least should be administered if possible, and the outcome of the patients who discontinued BR after four cycles was not inferior to that of the cases who received five or six cycles. In conclusion, discontinuation after four cycles may be permissible in some cases with complete response to BR regimen.